Mycotic infection as a risk factor for COVID-19: A meta-analysis - Liu, Anlin; Li, Zhengtu; Su, Guansheng; Li, Ya; Zhang, Yuzhuo; Liang, Jinkai; Cheng, Xiaoxue; Wang, Xidong; Li, Yongming; Ye, Feng (Frontiers in Public Health, 2022)
More than 405 million people have contracted coronavirus disease 2019 (COVID-19) worldwide, and mycotic infection may be related to COVID-19 development. There are a large number of reports showing that COVID-19 patients with mycotic infection have an increased risk of mortality. However, whether mycotic infection can be considered a risk factor for COVID-19 remains unknown. We searched the PubMed and Web of Science databases for studies published from inception to December 27, 2021. Pooled effect sizes were calculated according to a random-effects model or fixed-effect model, depending on heterogeneity. We also performed subgroup analyses to identify differences in mortality rates between continents and fungal species. A total of 20 articles were included in this study. Compared with the controls, patients with mycotic infection had an odds ratio (OR) of 2.74 (95% confidence interval (CI): 2.26-3.33) for mortality and an OR of 2.28 (95% CI: 1.65-3.16) for renal replacement therapy (RRT). We also conducted two subgroup analyses based on continent and fungal species, and we found that Europe and Asia had the highest ORs, while Candida was the most dangerous strain of fungi. We performed Egger’s test and Begg’s test to evaluate the publication bias of the included articles, and the p value was 0.501, which indicated no significant bias. Mycotic infection can be regarded as a risk factor for COVID-19, and decision makers should be made aware of this risk.